ON LIVING HADÎTS: A New Trend of Hermeneutics Approach to Study Hadîts in Indonesia - Saadeldin Mansour Gasmelsid; Khairil Husaini Bin Jamil; Alhafidh Nasution (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2026)
The Living Hadîts interprets hadîts through the cultural and social practices alive in Indonesian society. This method offers contextual sensitivity and involves hermeneutical, anthropological, and phenomenological frameworks. However, this approach also raises epistemological and methodological concerns—particularly regarding the integrity of isnâd-matn authentication, the potential weakening of textual authority, and the risk of cultural syncretism inconsistent with Syarî‘ah. This study, using historical genealogical analysis and a literature review, evaluates whether the Living hadîts contributes to a valid understanding of the sunnah or deviates from the principles of hadîts science established by scholars. Therefore, the authors will examine how this approach is used and the challenges that arise when it is applied to the study of hadîts in Indonesia. It found that the Living Hadîts method fosters multiculturalism because the hadîts applied within society is influenced by the community’s diverse social and cultural contexts. As a result, the hadîts no longer refers to the application found in authoritative sources, such as the views of the Prophet’s companions or the statements of ‘ulamâ’ with authority in understanding hadîts. However, this study recommends integrating textual verification and methodological reflexivity into Hadith pedagogy in societal life to balance social relevance with normative Islamic scholarship.